AN ANALYSIS ON DEIXIS USED IN EDITOR’S CHOICE OF THE JAKARTA POST ONLINE EDITION - ZULKARNAEN, AKHMAD IVAN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keyword: Deixis, Types of Deixis and Article. Deixis is a study about language phenomena which discusses words that have a relative meaning. Deixis can be found in the spoken and written language. In this study, the writer intends to analyze deixis contained in sentences of the online newspaper articles. This study is conducted to find out, (1) deixis types contained in sentences of the article, (2) interpretations of deixis in sentences ofthe article. The writer uses Levinson’s theory in analyzing the data.This study is qualitative study since the writer analyzes three articles in Editor’s Choice in the Jakarta Post online edition. The data of this study were taken from the sentences that contain deictic expresssion in Editor’s Choice section since 17th January to 26th January 2013.In this study the writer found 87 deictic expressions in the 67 sentences. The deictic expressions are person deixis, place deixis, time deixis, discourse deixis and social deixis based on Stephen C. Levinson. According to the analysis, the writer finds 14 person deixis, 27 place deixis, 40 time deixis and 6 discourse deixis. The types of deixis most commonly found is time deixis because thesearticles mostly contain reports which describe about time of the event. The  second majority goes to the person deixis especially third person deixis. It refers to the referent not identified as the speaker or addressee in the context. First and second person deixis is not mostly used since refers to the speaker who produces the utterance because the articles less contain opinions report of interview. The third tendency goes to place deixis. It refers to the location of the event that reports by the journalist as well as has been shown in the context. Discourse deixis is used to connect the previous discourse to the surrounding text. There is no Social deixis in the articles since there are no sentences that show the social distinction among participant roles in the sentence.This study hopefully can provide appropriate references for further researcher to conduct the research in deixis area. The further researcher can compare deeply between deixis and pronoun in the data analysis. Not only focuses on the types of deixis but also analyzes the difference between the deixis and pronoun. Besides, the writer suggests to the further researcher uses the same theory but different in the data source, not only in written but also in spoken language such as daily conversation which can be formal or informal dialogue or in any literary work such as the spoken dialogue in the movie or drama.